Adenocarcinoma of the prostate with small cell component and low levels of prostate specific antigen - Vojinov, Saša; Popov, Mladen; Levakov, Ivan; Levakov Fejsa, Aleksandra; Jeremić, Dimitrije; Grbić, Dragan (Vojnosanitetski pregled, 2021)
Introduction.  Prostate cancer is one of the most common malignancies in men. The most common type is acinar adenocarcinoma. Small cell prostate cancer (SCPC) usually occurs together with coexisting prostate adenocarcinoma. Case report. A 72-years-old patient with voiding simptoms is presented. Initial level of prostate specific antigen (PSA) was 2.87 ng/mL. Twelve prostate biopsies were taken and in six of them neoplastic tissue was detected. The viewed tissue was most convenient to “small cell carcinoma“. Bone scintigraphy did not demonstrate dissemination of the cancer into the skeletal system. Multislice computed tomography (MSCT) of the pelvis did not reveal any special pathological changes. The patient underwent surgery – radical retropubical prostatectomy. Histopathological analysis revealed a poorly differentiated adenocarcinoma of the prostate with small cell carcinoma zones [Gleason score 5+5 (10), grade III, pT3bN1, stage IV]. Conclusion. Poorly differentiated adenocarcinoma of the prostate, especially in combination with SCPC, is an aggressive malignancy with most cases presenting with the extensive disease dissemination on diagnosis and poor prognosis. Small cell carcinomas of the prostate are extremely rare tumors of the neuroendocrine origin. Patients with mixed prostate cancer, compared to pure SCPC, have a better prognosis and greater survival rate. There is a lack of the evidence guiding treatment for SCPC.
Keywords: prostatic neoplasms; prostate-specific antigen; diagnostic techniques and procedures; prostatectomy; drug therapy; prognosis